NANANG SULISTYO, ENI ROSNIJA, ENDANG SUSILAWATI ENGLISH EDUCATION STUDY PROGRAM OF FKIP UNTAN, PONTIANAK EMAIL: NA2NG.23@GMAIL.COM - Sulistyo, Nanang; Rosnija, Eni; Susilawti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: This research investigated the effectiveness of using anime entitled ?Bakuman? in teaching writing narrative text to year-11 students of SMAN 4 Pontianak in academic year 2015/2016. It was a pre-experimental research which the sample was XI MIA 1. The technique of collecting data was measurement technique. The instruments to collect data were essay tests which were divided into pre-test and post-test. Both pre-test and post-test measured the students? ability in writing narrative text. Pre-test was administered before the treatment. Meanwhile, post-test was administered after the treatment. The data showed that the mean score of pre-test was 78.88 and post-test was 82.38. The interval between the mean score of pre-test and post-test was 3.5. Based on the data analysis, the effect size was 0.44. It was categorized as ?modest effect?. Thus, the researcher concluded that the use of anime entitled ?Bakuman? was effective in teaching writing narrative text. Keywords: Writing, Narrative Text, Anime, Bakuman Abstract: Penelitian ini meneliti keefektifan penggunaan anime berjudul ?Bakuman? dalam mengajar menulis teks naratif pada siswa SMAN 4 Pontianak kelas 11 tahun ajaran 2015/2016. Penelitian ini merupakan sebuah penelitian eksperimental dengan sampel XI MIA 1. Teknik pengumpulan data yang digunakan adalah teknik pengukuran. Alat-alat pengumpulan data berupa tes esai yang dibagi menjadi pre-tes dan post-tes. Keduanya mengukur kemampuan siswa dalam menulis teks naratif. Pre-tes diberikan sebelum melakukan perlakuan. Sementara, post-tes diberikan setelah perlakuan. Data menunjukkan bahwa nilai rata-rata pre-tes adalah 78,88 dan post-tes adalah 82.38. Interval antara nila rata-rata pre-tes dan post-tes adalah 3,5. Berdasarkan analisis data, ukuran efek adalah 0.44 dikategorikan sebagai ?efek sedang?. Dengan demikian, dapat disimpulkan bahwa penggunaan anime berjudul ?Bakuman? efektif dalam mengajar menulis teks naratif. Kata kunci: Menulis, Teks Naratif, Anime, Bakuman